EVALUASI PARTISIPATORIS TERHADAP PELATIHAN PENDAMPINGAN KOMUNITAS DIFABEL DI DAERAH ISTIMEWA YOGYAKARTA - Fathur Rahman (Jurnal Penelitian Humaniora, 2008)
The objective of this research were to scrutinize the following problems; 1) to describe the impact of materials and training method on attitude changes and critical consciousness of difabel volunteers. 2) to explore how the volunteer’s experience by analizing their reflection on training program. 3) to describe the means of action plan and their implementation. There are several conclusions that can be drawn from the study. The first conclusion is that the training program involved materials and participating training methods gave a positive contribution to the attitude change of volunteer in understanding of shifting paradigm of rehabilitation to advocacy. It can be seen at an integrated and cohesive system of training that is designed to interact each other. Second, research findings show that the volunteer learned something practical that connects to their everyday activities. because the learning is experiential as the difabel partner, they not only learn about counseling and paralegal skills but also they learn how disability and its stigmatization are structural. Third, the action plans and follow-up program designed by volunteers can be concluded as one of successful indicators of training program. The action plans were conducted by volunteers includes dissemination activities, policy advocacy, building teamwork, cases conference.